Private transfers, public transfers, and foodinsecurity during the time of COVID-19: Evidence from Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Gilligan, Daniel O.; Hoddinott, John F.; Roy, Shalini (Agricultural and Applied Economics Association, 2023)
In the aftermath of the COVID-19 pandemic, interest has grown in what kinds of assistance protect household food security during shocks. We study rural and urban Bangladesh from 2018 to 2019 to late 2021, assessing how pre-pandemic access to social safety net programs and private remittances relate to household food insecurity during the pandemic. Using longitudinal data and estimating differences-in-differences models with household fixed effects, we find that pre-pandemic access to social protection is associated with significant reductions in food insecurity in all rounds collected during the pandemic, particularly in our urban sample. However, pre-pandemic access to remittances shows no similar protective effect.